Mapping a sector's scope transformation and the value of following the evolving core - Nicola Cetorelli; Michael G. Jacobides; Samuel Stern (Federal Reserve Bank of New York, 2021)
A surprisingly neglected facet of sector evolution is the evolutionary analysis of firms', and thus a sector's, scope. Defining a sector as a group of firms that can change their scope over time, we study the transformation of U.S. banking firms. We undertake a sectoral, population-wide study of business-scope transformation, with particular focus on which segments banks expand into. As financial intermediation evolved, a continuously shifting set of activities became associated with "core banking," with scope changing and relatedness itself (measured through coincidence) evolving over the banking sector's history. Banks that expand scope while staying close to this evolving core attain net performance benefits. Identification tests show that the benefits of following the evolving core are robust to endogeneity.
Keywords: G21; L23; D22; 330; scope; relatedness; diversification; industry evolution; expansion